Characterization of an activation‐tagged mutant uncovers a role of GLABRA2 in anthocyanin biosynthesis in Arabidopsis. (17th June 2015) - Wang, Xiaoyu; Wang, Xianling; Hu, Qingnan; Dai, Xuemei; Tian, Hainan; Zheng, Kaijie; Wang, Xiaoping; Mao, Tonglin; Chen, Jin‐Gui; Wang, Shucai
Summary In Arabidopsis, anthocyanin biosynthesis is controlled by a MYB‐bHLH‐WD40 (MBW) transcriptional activator complex. The MBW complex activates the transcription of late biosynthesis genes in the flavonoid pathway, leading to the production of anthocyanins. A similar MBW complex regulates epidermal cell fate by activating the transcription of GLABRA2 (GL2), a homeodomain transcription factor required for trichome formation in shoots and non‐hair cell formation in roots. Here we provide experimental evidence to show that GL2 also plays a role in regulating anthocyanin biosynthesis in Arabidopsis. From an activation‐tagged mutagenized population of Arabidopsis plants, we isolated a dominant, gain‐of‐function mutant with reduced anthocyanins. Molecular cloning revealed that this phenotype is caused by an elevated expression of GL2, thus the mutant was named gl2‐1D. Consistent with the view that GL2 acts as a negative regulator of anthocyanin biosynthesis, gl2‐1D seedlings accumulated less whereas gl2‐3 seedlings accumulated more anthocyanins in response to sucrose. Gene expression analysis indicated that expression of late, but not early, biosynthesis genes in the flavonoid pathway was dramatically reduced in gl2‐1D but elevated in gl2‐3 mutants. Further analysis showed that expression of some MBW component genes involved in the regulation of late biosynthesis genes was reduced in gl2‐1D but elevated in gl2‐3 mutants, and chromatin immunoprecipitation results indicated that some MBW component genes are targets of GL2. We also showed that GL2 functions as a transcriptional repressor. Taken together, these results indicate that GL2 negatively regulates anthocyanin biosynthesis in Arabidopsis by directly repressing the expression of some MBW component genes.